2016
DOI: 10.1021/acscentsci.6b00172
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery via Cell Membrane Fusion Using Lipopeptide Modified Liposomes

Abstract: Efficient delivery of drugs to living cells is still a major challenge. Currently, most methods rely on the endocytotic pathway resulting in low delivery efficiency due to limited endosomal escape and/or degradation in lysosomes. Here, we report a new method for direct drug delivery into the cytosol of live cells in vitro and invivo utilizing targeted membrane fusion between liposomes and live cells. A pair of complementary coiled-coil lipopeptides was embedded in the lipid bilayer of liposomes and cell membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
170
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(172 citation statements)
references
References 63 publications
1
170
0
1
Order By: Relevance
“…[27,47] So far, this approach was used to deliver low molecular weight dyes and drugs into the cytosol and nucleus of live cells. To study the scope of this synthetic fusion system, we now were interested to study whether coiled-coil mediated fusion could be used to enhance the intracellular delivery of inorganic nanoparticles like MSNs.…”
Section: Intracellular Delivery Of Cytcmentioning
confidence: 99%
See 1 more Smart Citation
“…[27,47] So far, this approach was used to deliver low molecular weight dyes and drugs into the cytosol and nucleus of live cells. To study the scope of this synthetic fusion system, we now were interested to study whether coiled-coil mediated fusion could be used to enhance the intracellular delivery of inorganic nanoparticles like MSNs.…”
Section: Intracellular Delivery Of Cytcmentioning
confidence: 99%
“…[27,[50][51][52][53][54] In this study, wortmannin (Wor) was used as a micropinocytosis inhibitor as it blocks PI3-kinase, [50,52,55,56] while genistein (Gen) inhibits tyrosine-phosphorylation of Cav 1 and caveolin-dependent endocytosis. [57][58][59] Furthermore, chlorpromazine (Chl) was used as it blocks clathrin-dependent endocytosis, [51,60,61] and microtubule formation was inhibited by nocodazole (Noc).…”
Section: Endocytosis and Micropinocytosis Inhibitors Marginally Affecmentioning
confidence: 99%
“…[3][4][5] More than 20 years ago, it was accidentlyd iscovered that certain protein domains, enriched in cationic amino acids, were responsible for promoting the translocation of some proteins throught he plasma membrane of cells. In 1997, Lebleu et al reportedt hat the peptidef unction of penetrating properties was attributed to the cationic domain, which was called the TATp eptide( TAT [49][50][51][52][53][54][55][56][57] ,R KKRRQRRR). In 1997, Lebleu et al reportedt hat the peptidef unction of penetrating properties was attributed to the cationic domain, which was called the TATp eptide( TAT [49][50][51][52][53][54][55][56][57] ,R KKRRQRRR).…”
Section: Introductionmentioning
confidence: 99%
“…The group of Wender at Stanford University systematically studied the TAT [49][50][51][52][53][54][55][56][57] peptide sequence and artificial analogues, and demonstrated that between eight and ten cationic amino The cell membrane regulates the exchange of molecules and information with the externale nvironment. However,t his control barrier hinders the delivery of exogenous bioactive molecules that can be appliedt oc orrect cellular malfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently have initial examples of in vivo targeted membrane fusion been reported using coiled coil peptides attached onto membrane surfaces. 47,48 Bioorthogonal chemistry presents a promising strategy for attaining this goal due to the selectivity of these reactions in complex biological environments. 49,50 We and others have shown that the derivatization of intact liposomes can be conveniently achieved using bioorthogonal reactions, such as the copper-catalyzed azide-alkyne cycloaddition (CuAAC), 5156 the strain promoted alkyne-azide cycloaddition (SPAAC), 5759 and the Staudinger ligation.…”
Section: Introductionmentioning
confidence: 99%